The autism "epidemic": Ethical, legal, and social issues in a developmental spectrum disorder. (4th April 2017) - Graf, William D.; Miller, Geoffrey; Epstein, Leon G.; Rapin, Isabelle
Abstract : Classic autism has gradually evolved into the concept of a larger "spectrum disorder." The rising prevalence of autism and autism spectrum disorder (autism/ASD) diagnoses can be largely attributed to broader diagnostic criteria, adoption of dimensional assessment strategies, increased awareness, linking of services to diagnosis, and the inclusion of milder neurodevelopmental differences bordering on normality. The spectrum disorder diagnosis raises numerous bioethical issues for individuals and society. Three groups of caregivers have important ethical, legal, and social obligations to individuals with autism/ASD: (1) families and advocates of individuals with autism/ASD; (2) health care and other professionals; and (3) governments. Each group may have different views of autism/ASD diagnostic criteria, screening, testing, and the effectiveness of various interventions. All see timely diagnosis as desirable, but earlier diagnosis may not be better, morally or practically. The growing practice of genetic testing in milder ASD raises ethical questions because of its uncertain scientific validity and limited clinical utility. Individuals with autism/ASD have various kinds of needs but all want acceptance and most deserve better accommodations. Governments struggle to provide a fair allocation of appropriate special education and supportive services. This article examines the evolving dimensions of the autism/ASD diagnosis, outlines certain bioethics principles related to its evaluation and management, reviews relevant laws and disability rights, and emphasizes the societal obligation to recognize neurodevelopmental variation and human neurodiversity. Future directions in the evaluation and care of autism/ASD should attempt to integrate the roles and responsibilities of all agents caring for each unique autistic individual.